PENYULUHAN HUKUM TENTANG BAHAYA NARKOBA DAN KENAKALAN REMAJA DI MTsN 05 PULO AMPEL - Fatari, Fatari; Afiah, Efi Tajuroh; Samsinar, Ade; Nurizki, Aris Trismayadi; Silalahi, Suandi; Kuraisin, Icin; Purwanti, Ranti; Hapidoh, Siti (Yayasan Education and Social Center, 2025)
Drug abuse and juvenile delinquency are serious issues with significant implications for the future of Indonesia’s young generation, particularly among students of productive age. This community service activity was conducted in the form of legal counseling aimed at educating teenagers about the dangers of drugs and the legal consequences of deviant behavior. The methods employed included interactive lectures, group discussions, and legal case simulations to encourage active participation. The program was implemented at MTsN 05 Pulo Ampel, involving students as the main participants. The results indicated an increased understanding among participants regarding the risks of drug abuse, its impact on health and future prospects, and the importance of avoiding delinquent behavior. This activity is expected to serve as a preventive measure to reduce drug abuse and misconduct among teenagers while strengthening legal awareness from an early age.